1967
DOI: 10.1002/aja.1001210105
|View full text |Cite
|
Sign up to set email alerts
|

Efferent fibers of the subthalamic nucleus in the monkey. A comparison of the efferent projections of the subthalamic nucleus, substantia nigra and globus pallidus

Abstract: A study was made to determine the efferent projections of the subthalamic nucleus in the monkey. Because of the impossibility of producing lesions in this nucleus, not involving adjacent structures, lesions were produced by different stereotaxic approaches. Comparisons were made with degeneration resulting from localized lesions in substantia nigra and globus pallidus. Degeneration resulting from these lesions was studied in transverse and sagittal sections stained by the NautaGygax method.Efferent fibers from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

1970
1970
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(33 citation statements)
references
References 47 publications
2
30
0
1
Order By: Relevance
“…The pallidum gets its afferents from the striatum, the nucleus centromedialis thalami (Mettler 1945 ;Nauta and Whitlock 1954 ;Johnson 1961), the subthalamic nucleus (Whittier and Mettler 1949 ;Carpenter and Strominger 1967) (Johnson and Clemente 1959), the nucleus interstitialis (Hassler 1956), and the lem-niscus medialis (Mettler 1945), whereas afferents from the cerebellum are not unchallenged (Mettler 1968) and those from the cortex are questionable (Truex and Carpenter 1969) . Furthermore there are the afferents from the contralateral pallidum .…”
Section: Atypical Chorea Imentioning
confidence: 99%
“…The pallidum gets its afferents from the striatum, the nucleus centromedialis thalami (Mettler 1945 ;Nauta and Whitlock 1954 ;Johnson 1961), the subthalamic nucleus (Whittier and Mettler 1949 ;Carpenter and Strominger 1967) (Johnson and Clemente 1959), the nucleus interstitialis (Hassler 1956), and the lem-niscus medialis (Mettler 1945), whereas afferents from the cerebellum are not unchallenged (Mettler 1968) and those from the cortex are questionable (Truex and Carpenter 1969) . Furthermore there are the afferents from the contralateral pallidum .…”
Section: Atypical Chorea Imentioning
confidence: 99%
“…IB). These GPl-subthalamic fibers, like the striato-nigral fibers, perforate the cere bral peduncle as components of the fasciculus lenticularis (FL) or 'comb' system [Nauta and Mehler, 1966;Carpenter and Strominger, 1967;Kuo and Carpenter, 1973].…”
Section: Connections and Projections Of The Globus Pallidusmentioning
confidence: 99%
“…The results of analysis of the efferent connections of the subthalamic nucleus by Carpenter and Strominger [1967] indicate that the nucleus projects mainly to the medial pallidus (GPm) ( fig. ID), a finding suggesting a relative short subcortical circuit: lateral GP->-subthalamic nucleus-vmedial GP.1 It should be noted that all three components of this circuit are selectively vulnerable to man ganese intoxication [Pentschew et al, 1963].…”
Section: Connections and Projections Of The Globus Pallidusmentioning
confidence: 99%
“…The STN neurons in primates also project to the contralateral GP via the dorsal supraoptic decussation. 15 The strength of this efferent connection is currently unknown but may contribute to the results observed here. More studies are warranted to assess this observed discrepancy in outcomes between ipsi-and contralateral subthalamotomy.…”
Section: Nmda Nr1/nr2b Receptor Bindingmentioning
confidence: 87%